Developing English worksheet of procedure twxt at the ninth grade students' reading comprehension - Khidayatul Munawwaro; Syamsiah depalina siregar; Efa Silfia; Muhammad khidayatullah Irfan; Mega Mega (Universitas Batanghari Jambi, 2026)
This study aims to develop English worksheets based on procedure texts to improve ninth-grade students’ reading comprehension. Using a Research and Development (R&D) design, the study involved needs analysis, product development, validation, and implementation. The results showed that the developed worksheets were appropriate and effective in enhancing students’ understanding of procedure texts, as well as increasing their engagement in learning.